PENGARUH DOSIS EKSTRAK JAMBU BIJI (PSIDIUM GUAJAVA. L) DAN TABLET Fe TERHADAP PERUBAHAN KADAR HEMOGLOBIN PADA MENCIT (MUS MUSCULUS) - Yusnaini, Yusnaini (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2016)
According to the WHO 40% of maternal deaths in developing countries related to anemia in pregnancy and is most commonly caused by iron deficiency and acute bleeding, even less so the two interact. This study aims to determine the effect of doses of extracts of Guava (Psidium Guajava. L) and Tablet Fe to changes in hemoglobin levels in mice (Mus musculus). Type True Experimental studies in laboratory design nonrandomized design Pretest-Posttest Control Group Design. Samples were mice (Mus musculus) as many as 20 birds were divided into four groups with each group number as many as five tails. Group A was given a tablet Fe as much as 0.126 mg / kg / day, group B was given a tablet Fe as much as 0.126 mg / KgBW / day coupled with extracts of Guava as much as 10 mg / kg / day, group C was given tablets Fe as much as 0.126 mg / kg / day coupled with guava extract as much as 20 mg / kg / day, group D was given tablets as much as 0.126 mg Fe / KgBW / day plus guava extract as much as 30 mg / kg / day. The data collection was conducted from June 5 s / d July 20, 2015. Data were analyzed using Paired T-Test continued with Test and One Way ANOVA Post Hoc Test namely LSD test. Results showed that there was no significant difference in hemoglobin levels between the groups in which the value of P = 0634> 0.05.. Based on the results of this study concluded that there was no effect of dose of extract of guava (Psidium Guajava. L) and Tablet Fe to changes in hemoglobin levels in mice (Mus musculus), but the effect on the number of erythrocytes of mice (Mus musculus)